Advanced coupler and filter design for microwave applications - Li, Xin. (2012)
Microwave coupler and filter are two crucial passive components widely used in the modern microwave communication systems and radar systems. Today’s wireless technology is moving to the multiple-band and multiple standard operations[1]. Single passive components like single coupler or filter can be made as small as possible and operate in dual or multiple bands in order to reduce both the size and cost [2].Thus in this project, operation of dual-band branch line coupler and rat-race coupler are investigated and dual-band couplers operating at 2.4GHz and 5GHz are designed and simulated using Advanced Design System (ADS). Secondly, new configurations of band-pass filters are proposed to realize steep roll-off, ultra wide stopband and compact size performances. 2.4GHz band-pass filters using the proposed structure are designed and simulated. The proposed structure is further modified into cascaded structure and additional coupled line structure to improve the overall performance. 2.4GHz band-pass filters utilizing those structures are designed and simulated. Dual-band operation of the structure is also investigated and dual-band band-pass filters operating at 2.4GHz and 5GHz are designed in this project.